2015
DOI: 10.1093/treephys/tpv024
|View full text |Cite
|
Sign up to set email alerts
|

Allocation dynamics of recently fixed carbon in beech saplings in response to increased temperatures and drought

Abstract: The response of carbon allocation to drought has often been studied in terms of short-term transport velocity of recently fixed carbon from leaves to roots and root respiration. However, its dynamic response to other environmental conditions, e.g., to changes in temperature, is less clear. Here, we investigated the effects of drought, increased temperatures and their combination on transport velocity as well as on distribution of recent photoassimilates for different compounds, such as sugars, starch, organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 62 publications
3
59
1
Order By: Relevance
“…Moreover, the 13 C excess in leaf WSOM, as a measure of the total uptake and conversion of 13 CO 2 to soluble sugars, was also not affected by the drought treatment. This is in agreement to the findings of Blessing et al (2015), but contradicts the observations of Ruehr et al (2009) for beech. The latter authors found clearly higher maximum d 13 C and 13 C excess in leaf WSOM in controls compared to drought-treated plants directly after labelling.…”
Section: The Effect Of Moderate Drought On Allocation Of New Assimilasupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, the 13 C excess in leaf WSOM, as a measure of the total uptake and conversion of 13 CO 2 to soluble sugars, was also not affected by the drought treatment. This is in agreement to the findings of Blessing et al (2015), but contradicts the observations of Ruehr et al (2009) for beech. The latter authors found clearly higher maximum d 13 C and 13 C excess in leaf WSOM in controls compared to drought-treated plants directly after labelling.…”
Section: The Effect Of Moderate Drought On Allocation Of New Assimilasupporting
confidence: 82%
“…Moreover, it is necessary to consider the fate of newly assimilated carbohydrates in different plant tissues as well as the long-distance transport via the phloem (Paterson et al 2009;Ruehr et al 2009;Offermann et al 2011) to understand the biomass allocation dynamics as well as root functioning in plants under changing environmental conditions (Blessing et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in starch with no significant shifts in sucrose and glucose + fructose at day 2 may indicate the allocation of NSC to metabolic maintenance and repair in response to the 45‐min treatment (Bita & Gerats, 2013). This may also be due to increased respiration (Way & Yamori, 2014), as well as the remobilization of starch from source leaves to roots (Blessing, Werner, Siegwolf, & Buchmann, 2015), although we did not measure NSC in roots. By days 15 and 25, total NSC, starch, and sucrose of the 45‐min group had significantly accumulated compared to controls, coinciding with the full recovery of photosynthesis and F V / F M .…”
Section: Discussionmentioning
confidence: 99%
“…Also, soluble sugars such as sucrose are among the primary metabolites and osmolytes known to accumulate in response to heat stress (Wahid et al., 2007) and are necessary for protection from elevated temperature and maintaining water balance and membrane stability (Bita & Gerats, 2013; Farooq et al., 2008). Sucrose is translocated from source leaves to sink organs through the phloem, and its transient increase in plants subjected to 90 min of heat stress may also be associated with a disruption or inhibition of phloem transport (Blessing et al., 2015; Sala et al., 2012; Woodruff, 2014). The subsequent decline in sucrose after day 2 suggests that the demand for sucrose for repair, renewed growth, and ongoing metabolism was greater than the supply from photosynthesis, which was still inhibited on day 50.…”
Section: Discussionmentioning
confidence: 99%